2020
DOI: 10.1109/access.2020.2990678
|View full text |Cite
|
Sign up to set email alerts
|

Is Technological Innovation Effective for Energy Saving and Carbon Emissions Reduction? Evidence From China

Abstract: Technological innovation is increasingly becoming an important way to develop a lowcarbon economy. Recently, exploring the driving path of low-carbon development has become the hot topic, however, the role of energy consumption in the carbon-reduction effect of technological innovation has been ignored. Based on China's provincial-level panel data from 2005 to 2016, this paper investigates the effect of technological innovation on energy saving and carbon emissions reduction and the role of energy consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Hence, Liu et al (2022) paper put it succinctly, "a country can not only realize technological progress through independent innovation, but also through technology spillover of foreign trade and global investment". Considering the global rapid economic growth and development with the expected increase in energy demand, numerous studies have sought to examine the relationship between technological innovation and energy demand (Liu et al, 2021;Zhu et al, 2021;Li et al, 2021;Zeraibi et al, 2020;Zhang et al, 2020;Murad et al, 2019;Grushevenko et al, 2018;Dudin et al, 2017;Zhang and Lu, 2015;Chou, 2015). But to our knowledge, most of these studies examine the direct impact of technological innovation on energy consumption, and the analysis are often in country-specific framework (Li and Solaymani, 2021;Zhang et al, 2020;Grushevenko et al, 2018;Chou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, Liu et al (2022) paper put it succinctly, "a country can not only realize technological progress through independent innovation, but also through technology spillover of foreign trade and global investment". Considering the global rapid economic growth and development with the expected increase in energy demand, numerous studies have sought to examine the relationship between technological innovation and energy demand (Liu et al, 2021;Zhu et al, 2021;Li et al, 2021;Zeraibi et al, 2020;Zhang et al, 2020;Murad et al, 2019;Grushevenko et al, 2018;Dudin et al, 2017;Zhang and Lu, 2015;Chou, 2015). But to our knowledge, most of these studies examine the direct impact of technological innovation on energy consumption, and the analysis are often in country-specific framework (Li and Solaymani, 2021;Zhang et al, 2020;Grushevenko et al, 2018;Chou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the global rapid economic growth and development with the expected increase in energy demand, numerous studies have sought to examine the relationship between technological innovation and energy demand (Liu et al, 2021;Zhu et al, 2021;Li et al, 2021;Zeraibi et al, 2020;Zhang et al, 2020;Murad et al, 2019;Grushevenko et al, 2018;Dudin et al, 2017;Zhang and Lu, 2015;Chou, 2015). But to our knowledge, most of these studies examine the direct impact of technological innovation on energy consumption, and the analysis are often in country-specific framework (Li and Solaymani, 2021;Zhang et al, 2020;Grushevenko et al, 2018;Chou et al, 2015). Nevertheless, few studies have examined how and whether other economic determinants drive the impact of technological innovation on energy consumption (Uddin et al, 2022 -financial development;Lin and Chen, 2020 -non-ferrous metal).…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al further considered the spatial distribution characteristics of carbon emissions, studied the spillover effect of carbon emissions in the Yangtze River Economic Belt and the driving path of technological innovation and found that cross-regional technological innovation in energy conservation and emission reduction can reduce carbon dioxide emissions and promote regional green development transformation [10]. Zhang et al used a linear regression model and mediating effects to verify the emission reduction effect of technological innovation and found that technological innovation effectively reduced carbon emissions in Chinese provinces, but energy consumption affected the emission reduction effect of technological innovation to some extent [11]. Cheng et al further considered the heterogeneity between regions in China and used quantile regression to synthesize the potential heterogeneous effects between energy technology innovation and carbon emission intensity in different regions of China [12].…”
Section: Introductionmentioning
confidence: 99%
“…As the world's second-largest economy, China has received widespread attention for its environmental pollution, especially its carbon emissions [1]. China consumed 4.64 billion tons of standard coal in 2018, an increase of 1.434 billion tons compared to a decade ago, with total carbon emissions of about 10 billion tons, more than the combined carbon emissions of the United States and the European Union, making it the world's largest energy consumer and carbon dioxide emitter [2].…”
Section: Introductionmentioning
confidence: 99%